2017
DOI: 10.1093/annonc/mdw611
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib versus gefitinib in patients with EGFR mutation-positive advanced non-small-cell lung cancer: overall survival data from the phase IIb LUX-Lung 7 trial

Abstract: BackgroundIn LUX-Lung 7, the irreversible ErbB family blocker, afatinib, significantly improved progression-free survival (PFS), time-to-treatment failure (TTF) and objective response rate (ORR) versus gefitinib in patients with epidermal growth factor receptor (EGFR) mutation-positive non-small-cell lung cancer (NSCLC). Here, we present primary analysis of mature overall survival (OS) data.Patients and methodsLUX-Lung 7 assessed afatinib 40 mg/day versus gefitinib 250 mg/day in treatment-naïve patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
379
3
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(439 citation statements)
references
References 26 publications
23
379
3
14
Order By: Relevance
“…Median OS was not significantly different between treatment arms (27.9 months with afatinib vs 24.5 months with gefitinib; HR: 0.86; p = 0.2580). However, LUX-Lung 7 was not powered for OS, as the sample size was based on controlling the width of the CI for the HR of PFS [29]. As in LUX-Lung 3 and LUX-Lung 6, the efficacy findings were generally consistent across patient subgroups of gender, age and ethnicity.…”
Section: Median Duration Of Response Months (95% Ci)mentioning
confidence: 99%
“…Median OS was not significantly different between treatment arms (27.9 months with afatinib vs 24.5 months with gefitinib; HR: 0.86; p = 0.2580). However, LUX-Lung 7 was not powered for OS, as the sample size was based on controlling the width of the CI for the HR of PFS [29]. As in LUX-Lung 3 and LUX-Lung 6, the efficacy findings were generally consistent across patient subgroups of gender, age and ethnicity.…”
Section: Median Duration Of Response Months (95% Ci)mentioning
confidence: 99%
“…However it has not been translated into an OS benefit. Indeed at a median follow-up of 42.6 months only a trend toward a better OS has been observed in patients receiving afatinib (27.9 vs 24.5 months) which did not reach statistical significance (HR: 0.86, 95%CI: 0.66-1.12) (Paz-Ares et al, 2017b). Even if OS data are still immature, LL7 can be formally defined as a negative trial.…”
Section: Direct Comparisonsmentioning
confidence: 99%
“…Since the approval of the first EGFR-TKI gefitinib in clinical setting, several other compounds have been developed by pharma, which may be classified as first, second, and third-generation EGFR-TKIs. About eight phase III randomized clinical trials compared EGFR-TKI Gefitinib, Erlotinib, or Afatinib vs platinum-based chemotherapy as first-line treatment for EGFR-mutated NSCLC patients (Reis-Filho and Pusztai, 2011;Mitsudomi et al, 2010;Maemondo et al, 2010;Paz-Ares et al, 2017a;Network CGA, 2012;Zhou et al, 2011;Sequist et al, 2011;Wu et al, 2014). The results of all such studies convincingly and consistently demonstrated a significant superiority of EGFR-TKIs over standard platinum-chemotherapy, improving both response rate (RR), progression free survival (PFS) and quality of life (QoL) of EGFR-mutated NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Частота любых НЯ ≥ 3 степени тяжести составляла 56,9% и 53,5%, а частота связанных с лечением НЯ ≥ 3 степени тяжести составляла 31,3% и 19,5% при лечении афатинибом и гефитинибом соответственно [70]. Такая же тенденция была замечена и при проведении другого сравнительного исследования ИТК-EGFR первого и второго поколений (эрлотиниба и афатиниба) LUX-Lung 8 в качестве второй линии терапии плоскоклеточного рака легкого.…”
Section: заключениеunclassified